Therapeutic effects of faricimab on aflibercept-refractory age-related macular degeneration - Ryosuke Tamiya; Masayuki Hata; Asako Tanaka; Memiri Tsuchikawa; Naoko Ueda-Arakawa; Hiroshi Tamura; Manabu Miyata; Ayako Takahashi; Ai Kido; Yuki Muraoka; Masahiro Miyake; Sotaro Ooto; et al. (Scientific Reports, 2023)
Abstract Though vascular endothelial growth factors (VEGF) and other proangiogenic factors, such as angiopoietins (Ang), may be involved in the development of neovascular age-related macular degeneration (nvAMD), only drugs that inhibit the VEGF family are available for the treatment. The newly approved anti-VEGF drug faricimab, which also inhibits Ang-2, is expected to be effective in patients with AMD refractory to conventional anti-VEGF drugs. Therefore, we prospectively investigated the efficacy of faricimab in the treatment of aflibercept-refractory nvAMD. Patients with nvAMD who had been treated with aflibercept in the last year and required bimonthly injections were recruited. 25 eyes showed persistent exudative changes immediately before the faricimab injection (baseline). In these 25 eyes, switching to faricimab did not change visual acuity or central retinal thickness 2 months after the injection; however, 56% of eyes showed reduction or complete absorption of fluid. Notably, 25% of the eyes that showed dry macula at month 2 had no fluid recurrence for up to 4 months. These results indicate that faricimab could benefit some patients with aflibercept-refractory nvAMD.